ANALISIS PENGARUH MODIFIED DIMENSION OF E-SERVICE QUALITY TERHDAP E-LOYALTY YANG DIMEDIASI OLEH E-SATISFACTION PADA PENGGUNA APLIKASI LINK AJA - Malkan Yahya Abdillah; Arlina Nurbaity Lubis; Nismah Panjaitan (Universitas Islam Negeri Sumatera Utara, 2025)
This study aims to analyze how the Modified Dimensions of E-Service Quality including Efficiency, Reliability, Responsiveness, Fulfillment, and Privacy influence E-Satisfaction and E-Loyalty, both directly and indirectly, among LinkAja application users in Medan, Indonesia. The research uses a quantitative approach with primary data obtained from 100 respondents who are active users of the LinkAja e-wallet application. Data were analyzed using the Structural Equation Modeling (SEM) method with the SmartPLS 3.0 software. The results show that all five dimensions of E-Service Quality have a positive and significant effect on E-Satisfaction and E-Loyalty, both directly and indirectly through E-Satisfaction as a mediating variable. These findings indicate that user satisfaction plays a crucial role in fostering user loyalty toward digital payment applications. Therefore, improving efficiency, system reliability, service responsiveness, and user data privacy is essential to enhance overall user experience and strengthen customer loyalty to LinkAja.